Role of Family Ownership in the Relationship between Corporate Social Responsibility and Firm Performance - Doddy Setiawan; Andi Asrihapsari; Rayenda Khresna Brahmana; Harumi Puspa Rizky; Mega Wahyu Widawati (Complexity)
This study examines the effect of corporate social responsibility (CSR) on firm performance in Indonesia. Most Indonesian companies are family-owned; therefore, it is important to consider the family ownership’s role in the relationship between CSR and firm performance. The study sample consists of 285 Indonesian listed firms for the period 2015–2019. Our results show that CSR positively affects performance. Companies that conduct more CSR activities perform better, indicating their importance. Further, the interaction between family ownership and CSR negatively affects firm performance. Therefore, family ownership weakens the positive effects of CSR. Family owners have significant disincentives for the CSR’s positive effect in improving firm performance.